A Meta-Analytic Review of Entrepreneurial Orientation and Firm Performance: The Mediating Roles of Strategic and Dynamic Capabilities and the Moderating Effects of Contextual Factors - Rennie Bakashaba; Dedrix Stephenson Bindeeba (SEISENSE (PRIVATE) LIMITED, 2025)
Purpose: This study investigates the relationship between Entrepreneurial Orientation (EO) and firm performance (FP) by examining the mediating roles of Strategic Capabilities and Dynamic Capabilities, and the moderating effects of contextual factors such as geographic region and study period.Methodology: The research design employed a meta-analytic review that was conducted using data from 95 peer-reviewed empirical studies encompassing 19,555 firm-level observations. Comprehensive Meta-Analysis (CMA) software was employed to synthesize effect sizes, test mediation pathways, and explore moderation effects across contextual subgroups. The study follows PRISMA guidelines to ensure methodological rigor.Findings: The results confirm that EO positively influences firm performance both directly and indirectly. Strategic Capabilities exhibit a stronger mediating effect than Dynamic Capabilities, suggesting that deliberate resource orchestration enhances EO effectiveness. Contextual analysis reveals that the EO–performance link is more pronounced in emerging economies and in studies conducted after 2015, reflecting evolving entrepreneurial environments.Policy Implications: The findings underscore the need for policies that support capability development within SMEs, especially in emerging markets. Tailored interventions that enhance strategic alignment and dynamic responsiveness can amplify EO’s performance impact.Originality: Finally, this study is among the first to meta-analytically decompose the EO–Performance relationship through dual mediators and contextual moderators, advancing theoretical understanding and offering actionable insights.